Topiramate as a neuroprotective agent in a rat model of spinal cord injury - Firat Narin; Sahin Hanalioglu; Huseyin Ustun; Kamer Kilinc; Burcak Bilginer (Neural Regeneration Research, 2017)
Topiramate (TPM) is a widely used antiepileptic and antimigraine agent which has been shown to exert neuroprotective effects in various experimental traumatic brain injury and stroke models. However, its utility in spinal cord injury has not been studied extensively. Thus, we evaluated effects of TPM on secondary cellular injury mechanisms in an experimental rat model of traumatic spinal cord injury (SCI). After rat models of thoracic contusive SCI were established by free weight-drop method, TPM (40 mg/kg) was given at 12-hour intervals for four times orally. Post TPM treatment, malondialdehyde and protein carbonyl levels were significantly reduced and reduced glutathione levels were increased, while immunoreactivity for endothelial nitric oxide synthase, inducible nitric oxide synthase, and apoptotic peptidase activating factor 1 was diminished in SCI rats. In addition, TPM treatment improved the functional recovery of SCI rats. This study suggests that administration of TPM exerts neuroprotective effects on SCI.